Climate Change Sceptical Frames: The Case of Seven Australian Sceptics. (24th February 2017) - Van Rensburg, Willem; Head, Brian W.
Abstract : Climate change sceptics are known for their resistance to proactive climate response policies, especially policies aimed at restricting greenhouse gas emissions. It is often assumed that scepticism about the science behind climate change would lead directly to outright rejection of all proactive climate policies aimed at mitigating emissions and adapting to climate‐induced changes already under way. This article demonstrates the variability among the climate policy views of seven well‐known Australian climate change sceptics in the period 2007–2012. Using the lens of frame‐analysis, we unpack some key sceptic rationales and narratives. The analysis shows that sceptics share a master frame that privileges individualist‐libertarian‐progress‐social order values, which are thus likely to conflict with the values implicit in conventional climate policy remedies. The analysis also shows that sceptical pre‐occupations diverge at more detailed framing levels, with various practical concerns and fears often at the centre of sceptical argumentation